A Common Design-Features Ontology for Product Data Semantics Interoperability - Abdul-Ghafour, Samer; Ghodous, Parisa; Shariat, Behzad; Perna, Eliane (Proceedings of the IEEE/WIC/ACM International Conference on Web Intelligence, 2007)
In a collaborative design environment, various software tools are utilized to enhance the product development. This entails a meaningful representation and exchange of product data semantics across these different systems. Semantic interoperability of product information refers to enabling the exchange of design intelligence, including construction history, parameters, features, and constraints. This is a crucial difference compared to current standards such as STEP that deliver "dumb" geometry, where no design intent is associated. To enable semantics data exchange, we propose an ontology-based approach, consisting in developing a "Common Design Features Ontology", called CDFO. Interoperability among ontologies is fulfilled by defining several mapping rules. We use a descriptive logic-based language, notably OWL DL to represent formally our ontology.